Youth Religiosity and Da'wah Development in The LPKA Class II Detention Sukamiskin Bandung - Hikmat Hikmat (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
The purpose of this study, first to obtain empirical data on the level of adolescent religiosity of assisted residents in Rutan LPKA Class II Sukamiskin Bandung. Secondly, to obtain data on the development of da'wah and religious formation towards adolescent Guidance residents in the LPKA Class II Detention Center Sukamiskin Bandung. This study uses the Research and Development (R&D) method or research and development with a qualitative approach. The results showed that the religiosity of the assisted residents in the LPKA Prison was categorized into three, namely: the level of religion was very good, good enough and less, of the three categories determined the da'wah program and religious coaching at the Prison for Youth LPKA Sukamiskin Bandung. The development of da'wah and patterns of religious guidance for youth assisted residents at the Class II Sukamisnin Bandung Prison LPKA is carried out by involving various parties. As an institution, collaborating with the Ministry of Religious Affairs in Bandung and MUI in Bandung is carried out periodically and on a scheduled basis. Then with the local cleric figure, the leader of the Sukamiskin boarding school in developing da'wah about child worship and morals.Tujuan penelitian ini, pertama untuk mendapartkan data empirik tingkat religiusitas remaja warga binaan di Rutan LPKA Kelas II Sukamiskin Bandung. Kedua untuk mendapatkan data tentang pengembangan dakwah dan pebinaan keagamaan terhadap remaja warga Binaan di Rutan LPKA kelas II Sukamiskin Bandung. Penelitian ini menggunakan Metode Research and Development (R&D) atau penelitian dan pengembangan dengan pendekatan kualitatif. Hasil penelitian menunjukan bahwa, religiusitas warga binaan di Rutan LPKA dikatagorikan menjadi tiga yaitu: tingkat keagamaan sangat baik, cukup baik dan kurang, dari tiga katagori tersebut ditentukan program dakwah dan pembinaan kegamaan di Rutan remaja LPKA Sukamiskin Bandung. Pengembangan dakwah dan pola pembinaan keagamaan terhadap remaja warga binaan di Rutan LPKA kelas II Sukamisnin Bandung dilaksanakan dengan melibatkan berbagai pihak. Secara kelembagaan bekerja sama dengan Kementrian Agama kota Bandung, dan MUI kota Bandung, dilaksanakan secara periodik dan terjadwal. Kemudian dengan tokoh ulama setempat yakni pimpinan pesantren Sukamiskin dalam pengembangan dakwah tentang ibadah dan akhlak anak.